Co-pyrolysis of oil palm trunk and polypropylene: Pyrolysis oil composition and formation mechanism - Terry, L.M.; Wee, Melvin Xin Jie; Chew, J.J.; Khaerudini, D.S.; Timuda, G.E.; Aqsha, A.; Saptoro, Agus; Sunarso, J. (2023)
Pyrolysis oil can be used as a precursor to synthesize value-added biochemicals. Co-pyrolysis of two or more feedstocks generally improves the selectivity and yield of the target compounds. In this work, oil palm trunk (OPT) was subjected to single-feed pyrolysis and co-pyrolysis with polypropylene (PP) from 500 to 700 °C. The highest pyrolysis oil yield of 26.33 wt.% was obtained from OPT at 700 °C, which mainly contributed by the lignin decomposition in OPT. Phenolics (51.77–57.78%) and oxygenates (36.31–46.99%) were the major compounds detected in the OPT-derived pyrolysis oil. The addition of PP enhanced the formation of hydrocarbons (5.19–10.22%) and decreased the contents of phenolics (34.01–41.85%) in the co-pyrolysis oil. In the case of co-pyrolysis, the intermolecular reactions between PP and OPT-derived radicals led to the formation of ketones and alcohols, which contributed to the increase of oxygenates content. The highest oil yield of 16.17 wt.% was obtained at 600 °C from co-pyrolysis, the oil of which contained mainly phenolic compounds, oxygenated compounds (i.e., ketones and furans), and hydrocarbons. These findings highlighted the potential of oil derived from the pyrolysis of OPT (single feed) and co-pyrolysis of OPT and PP (binary feed) for the production of value-added chemicals.